Budaya Organisasi Memediasi Kualitas Penerapan Sistem Informasi Akuntansi dan Kepercayaan Teknologi Informasi Pada Kinerja Karyawan - Pratami, Luh Ayu Regita; Damayanthi, I Gusti Ayu Eka (E-Jurnal Akuntansi; Vol 22 No 2 (2018)DO - 10.24843/EJA.2018.v22.i02.p08, 2018)
Computer-based accounting information system is important to be applied in BPR to produce information in the form of relevant, accurate and timely financial report. Sustainability and success of an organization can be seen from the performance dimilliki by employees. It is expected that employees are able to complete the task and produce information in a timely, accurate, and reliable way. Organizations need to pay attention to factors that have an effect on employee performance. This study aims to determine the Effect of Quality of Accounting Information System Application and Trust of Information Technology on Employee Performance with Organizational Culture as Variable Mediasi.Teknik determination of the sample used is the technique of non probability sampling with purposive sampling method so that obtained sample of 90 samples. The data was collected by using survey method, which is distributing questionnaires to BPR employees in Gianyar Regency. The analysis technique used in this research is path analysis. The results showed that the quality of SIA application and IT trust influenced the organizational culture in BPR Kabupaten Gianyar. Organizational culture, Quality of SIA implementation and IT Trust influence on employee performance in BPR Kabupaten Gianyar. The quality of SIA implementation and IT belief through organizational culture has an effect on employee performance in Rural Bank of Gianyar. The results of this study can be used by subsequent researchers, as research materials in the field of science of organizational behavior or similar science. Keywords: Quality of accounting information system, it trust, employee performance, organizational culture